Using portfolio theory to predict the impact of reduction in product width on sales - Brzęczek, Tomasz (Journal of Business Economics and Management, 2016)
Modern portfolio theory was applied to research product portfolio diversification. Prior research studies claimed a positive relationship between the number and variety of products and sales smoothing. However, they have also argued the limitations of classical portfolio analysis, especially owing to the assumption of independence of portfolio shares and the static nature of the approach. To address this limitation we extend the model to fit the trend and seasonality of sales, and to cover their correlations. The model aims to predict the impact of product width reduction on sales and their volatility. We consider the reduction of a product category in portfolio. The model covers the impact of product category sales on portfolio sales but also on other product category sales. Finally, we verify the model using a wholesaler company’s data and compare results. Hence, we recommend the model for the prediction of changes in sales and their volatility due to product category reduction. The model covers the portfolio dynamic approach to product width under the assumption of price taking, unlike in product assortment and variety planning models.